An Epidemiologic Internet Survey of Fibromyalgia and Chronic Pain in Japan. Issue 7 (July 2014) - Nakamura, Ikuro; Nishioka, Kenya; Usui, Chie; Osada, Kenichi; Ichibayashi, Hisao; Ishida, Mitsuhiro; Turk, Dennis C.; Matsumoto, Yoshifuji; Nishioka, Kusuki
<x xml:space="preserve">Abstract</x> Objective To determine the epidemiologic features and symptom characteristics of fibromyalgia (FM) in Japan, and compare them with those for other chronic pain (CP) diagnoses. Methods An internet survey was conducted in June and July 2011. The questionnaire consisted of 111 questions, including assessments of the Japanese version of the 2010 American College of Rheumatology preliminary diagnostic criteria for FM, the Japanese Fibromyalgia Impact Questionnaire, and additional questions regarding pain and lifestyle. Results The questionnaire was completed by 20, 407 male and female respondents in all prefectures of Japan. Of the survey population, 2, 524 respondents (12.4%) reported symptoms consistent with CP; of these, 425 (2.1%) reported symptoms consistent with FM. Among respondents with FM and CP, 61% and 53%, respectively, were women. Pain severity and Widespread Pain Index scores were significantly higher in respondents meeting the diagnostic criteria for FM than in those meeting the criteria for CP. In terms of symptom severity scores, the proportions of respondents reporting the 3 major symptoms as "highly applicable" and greater numbers of 41 somatic symptoms were higher among respondents with FM than among those with CP. The incidence of FM in the present survey was similar to that reported (1.7%) in a study of FM in Japan in 2003, despite the use of the newer, easier to use 2010 diagnostic criteria. Conclusion Because FM usually presents with more severe and more widely distributed pain, as well as more nonpainful symptoms than CP, our results suggest that FM is a different clinical phenotype of CP.